The Influence of the Outdoor Study-Based Discovery Learning Model on the Critical Thinking Skills of Class X Students of State Senior High School 7, Kupang City - Maya Gracia Tifany Lobo; Sukmawati Sukmawati; Erry Ersani (Tinta Emas Publisher, 2025)
Modern education requires students to develop critical thinking skills to keep pace with rapid advances in science and technology. One instructional approach that can foster these skills is discovery learning integrated with outdoor study, which enables learners to construct understanding through direct field experiences. This study aimed to examine the effect of an outdoor study–based discovery learning model on the critical thinking skills of Grade 10 students at State Senior High School 7, Kupang City. Using a quantitative quasi-experimental design, the research involved two groups: an experimental class taught through outdoor study–based discovery learning and a control class taught through conventional instruction. Participants were Grade 10 students at State Senior High School 7, Kupang City. Data were collected through critical thinking tests, classroom observations, and documentation. Learning improvement was analyzed using the normalized gain (N-gain), while between-group differences were assessed using an independent-samples t-test. The discovery learning procedure comprised six stages—stimulation, problem statement, data collection, data processing, verification, and generalization—each embedded within outdoor study activities to help students connect theoretical concepts with observable phenomena in their surrounding environment. The results indicate that the outdoor study–based discovery learning model produced greater improvements in students’ critical thinking skills than conventional learning, as reflected in higher N-gain scores and statistically significant t-test outcomes. In conclusion, integrating outdoor study into discovery learning is effective for enhancing critical thinking in geography and can serve as a viable alternative strategy for teachers seeking to design meaningful learning experiences.